2008
DOI: 10.1093/cercor/bhn045
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Working Memory and Long-Term Memory in the Medial Temporal Lobe

Abstract: Recent findings indicate that regions in the medial temporal lobe (MTL) do not only play a crucial role in long-term memory (LTM) encoding, but contribute to working memory (WM) as well. However, very few studies investigated the interaction between these processes so far. In a new functional magnetic resonance imaging paradigm comprising both a complex WM task and an LTM recognition task, we found not only that some items were successfully processed in WM but later forgotten, but also that a significant numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 62 publications
2
52
1
3
Order By: Relevance
“…However, no significant effect of content was found during preparation or rehearsal stages. These results are inconsistent with previous studies that have implicated distinct roles for MTL regions object and spatial working memory (Stern et al, 2001;Petersson et al, 2006;Olson et al, 2006a,b;Nichols et al, 2006;Axmacher et al, 2007Axmacher et al, , 2008. Such studies have demonstrated a role of the MTL and inferior temporal cortex in active maintenance of novel information.…”
Section: Discussioncontrasting
confidence: 97%
“…However, no significant effect of content was found during preparation or rehearsal stages. These results are inconsistent with previous studies that have implicated distinct roles for MTL regions object and spatial working memory (Stern et al, 2001;Petersson et al, 2006;Olson et al, 2006a,b;Nichols et al, 2006;Axmacher et al, 2007Axmacher et al, , 2008. Such studies have demonstrated a role of the MTL and inferior temporal cortex in active maintenance of novel information.…”
Section: Discussioncontrasting
confidence: 97%
“…There is imaging evidence that the hippocampus is engaged during working-memory maintenance under certain circumstances, such as during maintenance of novel information (e.g., Ranganath et al 2001;Cabeza 2004), and a recent high-resolution fMRI study of mediotemporal lobe (MTL) subregions provided evidence that neurons in these regions may act as a workingmemory buffer for novel information (Schon et al 2015). In the introductory hypothetical scenario, the first code was retained hours later, and some studies have linked workingmemory-related brain activity to subsequent long-term memory and found that parahippocampal-sustained fMRI activity during active maintenance was correlated with later memory performance (Schon et al 2004;Axmacher et al 2008; see also Rudner et al 2007; for related intracranial EEG evidence, see Axmacher et al 2007). Relatedly, findings by Ben-Yakov and Dudai (2011) show that poststimulus hippocampus activity contributes to the registration into long-term memory of complex real-life information.…”
Section: How Is Information In Working Memorymentioning
confidence: 99%
“…Therefore, the effect of unsuccessful attempts to execute WM processes on LTM encoding could not be investigated. Using a WM task with a complex item manipulation, we recently found that parahippocampal activity predicted LTM formation only if the WM manipulation was executed successfully, whereas it was detrimental for LTM formation in incorrectly solved WM trials (Axmacher et al, 2008). This indicates that medial temporal regions may also be activated by unsuccessful attempts to perform a WM task, but that this activity actually deteriorates LTM formation.…”
Section: Relationship To Previous Studies On Wm-ltm Interactionsmentioning
confidence: 99%
“…Therefore, we do not know for sure how LTM is actually affected by the WM performance for specific items, i.e., it is unknown which items are actually maintained in WM. This is a problem which can only be addressed in tasks with both a WM and a LTM test (Schon et al, 2004;Ranganath et al, 2005;Axmacher et al, 2008). It would be interesting to extend these studies to lists with several items, although this would require a complex experimental design: To identify subsequent memory effects, items need to be presented individually.…”
Section: Relationship To Previous Studies On Wm-ltm Interactionsmentioning
confidence: 99%